Factors Affecting the Adoption of Electronic Customer Relationship Management Information Systems in SMEs - Olupot, Charles; Kituyi, Mayoka G.; Noguera, Jose (Journal of Studies in Social Sciences, 2014)
The recent global recession has pushed businesses to search for means to efficiently and effectively manage their customers so as to remain competitive. This has led to the rise in the adoption and use of information technology in different business functions. These developments have yielded into the adoption of Electronic Customer Relationship Management. However, as this technology sees more prominence in the developed countries, many organizations in developing countries are finding it difficult to implement. This study was intended to examine the factors that affect the adoption of Electronic Customer Relationship Management in developing countries. A case study was conducted in Uganda, in which 150 Small and Medium-sized Enterprises where purposively selected from 30 districts to participate in the study. A sample size of 450 was taken from these organizations. Self administered questionnaires were used to collect data. Te data were coded and analyzed using descriptive statistics. Findings indicate that although Electronic Customer Relationship Management was very beneficial in promoting Small and Medium Enterprises’ new products, marketing existing products, keeping their customers updated and sharing information, most Small and Medium Enterprises faced challenges in adopting the technology. The main challenges were highlighted as lack of knowledge about the Electronic Customer Relationship Management, lack of Information Communication Technology skills, poor infrastructure, lack of top management support and resistance to change. The study gives some recommendations for better adoption of Electronic Customer Relationship Management in Small and Medium Enterprises.
Keywords: e-CRM; SMEs; Information Systems; e-CRM adoption; Technology adoption; Uganda